International realtions - Goldstein, Joshua (1994)
The subject and its setting. Power politics. Foreing policy. Internacional conflict. Military force. International organization and law. Critiques of power politics. Trade. Money and business. Integration. The enviroment. The north-South gap. International development.
Keywords: Relaciones internacionales